MEMBINCANG PROSES ISLAMISASI KAWASAN KALIMANTAN DARI BERBAGAI TEORI - Rahmadi Rahmadi (UIN Antasari Banjarmasin, 2020)
This study discusses four issues related to the Islamization in Kalimantan, namely the origin of the arrival of Islam, the period of the arrival of Islam, the spreader of Islam, and the channels of Islamization. These four problems are studied using a historical approach by analyzing relevant information from various sources. This study concluded that the Islamization in Kalimantan led to an Arab theory, namely that Islam came to this area directly brought by Arabs themselves from the Middle East, both by traders and professional preachers (ulama or Sufi). Furthermore, the Islamization period of the Kalimantan region is divided into four phases, namely the arrival phase in the 7th to 10th centuries; the phase of formation of the Muslim community in the 11th to 15th centuries; the great wave phase of coastal Islamization and the formation of Islamic empires in the 16th to early 17th centuries; and the phase of Islamization from the coast to the interior that occurred in the 17th to 19th centuries. The carriers of Islam at the arrival stage (7th to 12th centuries) were traders, and at the development stage (13th to 17th centuries) were brought by professional preachers (wandering Sufi scholars). Finally, Islamization in Kalimantan was carried out using the channels of da'wah, politics, trade, marriage, and education.Kajian ini membahas empat masalah terkait islamisasi kawasan Kalimantan, yaitu asal kedatangan Islam, masa kedatangan Islam, pembawa Islam dan saluran Islamisasi. Keempat masalah ini dikaji menggunakan pendekatan sejarah dengan melakukan analisis terhadap informasi yang relevant dalam berbagai sumber sejarah. Kajian ini menghasilkan simpulan bahwa Islamisasi di kawasan Kalimantan mengarah ke teori Arab, yakni Islam datang ke kawasan ini dibawa langsung oleh orang Arab sendiri dari Timur Tengah baik oleh pedagang maupun pendakwah profesional (ulama atau sufi). Selanjutnya, periodesasi islamisasi kawasan Kalimantan terjadi dalam empat fase, yaitu fase kedatangan pada abad ke-7 hingga abad ke-10, fase pembentukan komunitas muslim pada abad ke-11 hingga 15, fase gelombang besar islamisasi pesisir dan pembentukan kerajaan Islam pada abad ke-16 hingga awal abad ke-17, dan fase islamisasi dari pesisir ke pedalaman yang tejadi pada abad ke-17 hingga abad ke-19. Adapun pembawa Islam pada tahap kedatangan (abad ke-7 hingga 12) adalah para pedagang dan pada tahap perkembangan (abad ke-13 hingga 17) dibawa oleh para pendakwah profesional (ulama sufi pengembara). Terakhir, islamisasi di Kalimantan dilakukan melalui saluran dakwah, politik, perdagangan, perkawinan, dan pendidikan.